Self-care and manual ability in preschool children with cerebral palsy: a longitudinal study - Burgess, A.; Boyd, Roslyn; Ziviani, J.; Ware, R.; Sakzewski, L. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Mac Keith Press Aim: To describe longitudinal development of self-care and its relationship to manual ability in children with cerebral palsy (CP) aged 18 months to 5 years across all functional abilities. Method: This was a prospective longitudinal population-based study of 290 children with CP (178 [61%] males, 112 [39%] females). Self-care was assessed using the Pediatric Evaluation of Disability Inventory (PEDI). At 60 months (n=242), children were classified using the Manual Ability Classification System (MACS); 113 in level I (47%), 61 in MACS level II (25%), 24 in MACS level III (10%), 14 in MACS level IV (6%), and 30 in MACS level V (12%). Measures were taken at 18 months, 24 months, 30 months, 36 months, 48 months, and 60 months of age. Longitudinal analyses were performed using mixed-effects linear regression models. Results: Self-care development achieved by 60 months was negatively associated with the severity of manual ability impairment. Distinct self-care developmental trajectories were found with estimated changes in PEDI self-care scaled scores per month: 0.61 for MACS level I, 0.46 for MACS levels II, 0.31 for MACS level III, 0.16 for MACS level IV, and 0.03 for MACS level V. Children classified in MACS level V had the lowest level of self-care skills at 18 months and showed no progress in self-care development. Interpretation: This study reports rate of self-care development in preschool children with CP. Self-care performance was highest in children with greatest manual ability. Clinicians may use rates of change to predict or monitor self-care performance. PEDI trajectories inform goal setting in discussions with families regarding expected levels of independence in self-care. What this paper adds: Distinct self-care developmental trajectories in children with cerebral palsy were found according to Manual Ability Classification System (MACS) levels. Children in MACS levels IV and V with epilepsy did not show any significant change in self-care. Children in MACS levels IV and V without epilepsy demonstrated small yet significant gains in self-care performance.